PENINGKATAN HASIL BELAJAR KOGNITIF SISWA KELAS X MAN LUWU MELALUI PENDEKATAN CTL DENGAN MODEL PICTURE AND STUDENT ACTIVE PADA MATA PELAJARAN SEJARAH - Nahar Bana (STKIP Pembangunan Indonesia Makassar, 2023)
This research is classroom action research with exposure fo qualitative descriptive data in the from of cumulative frequency data, the subject of research is a student of class X MAN luwu Kab. Luwu, data collection with oservation and testing techniques. The data analysis technique used is the statistical analysis of cumullative frequency distribution. The results of this study show that learning with the CTL approach model PaSA (Picture and Student Active) can improve the cognitive learning results of class X student. Luwu with an average total score of 80,64, or equivalent to the learning outcome above intensity. In connection with this, the researcherssuggested that other class teacher, especially class teacher X MAN Luwu Kab. Luwu, can apply learning with the approach CTL model PASA (Picture and Student Active) in presenting learning materials in order to optimeze the ability of students in solving issues of historial subjectsKeyword :Contextual learning approach, students learning outcome